2010
DOI: 10.4269/ajtmh.2010.10-0353
|View full text |Cite
|
Sign up to set email alerts
|

Limited Polymorphism of the Plasmodium vivax Merozoite Surface Protein 1 Gene in Isolates from Turkey

Abstract: Abstract. The 200-kD merozoite surface protein of Plasmodium vivax (PvMSP-1) is one of the leading vaccine candidates against P. vivax malaria. However, the gene encoding PvMSP-1 ( pvmsp1 ) is highly polymorphic and is a major obstacle to effective vaccine development. To further understand polymorphism in pvmsp1 , we obtained 30 full-length pvmsp1 sequences from southeastern Turkey. Comparative analysis of sequences from Turkey and other areas showed substantially limited polymorphism. Substitutions were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
1
16
0
2
Order By: Relevance
“…In the current study, we did not find any correlation between antibody responses to PvMSP1 19 and parasite number, suggesting the possibility of allelic polymorphisms in the antigen/parasites. In fact, in a recent study, we did find eight substitutions in the PvMSP1 gene that were unique to the Turkish P. vivax population and one of them (D/E at 1706 in the C-terminal 19-kDa region) was previously unidentified [17]. To understand whether this unique D/E substitution has impact on the antibody responses and parasite levels, we measured total IgG levels in a limited numbers of infected serum bearing the D/E substitution.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the current study, we did not find any correlation between antibody responses to PvMSP1 19 and parasite number, suggesting the possibility of allelic polymorphisms in the antigen/parasites. In fact, in a recent study, we did find eight substitutions in the PvMSP1 gene that were unique to the Turkish P. vivax population and one of them (D/E at 1706 in the C-terminal 19-kDa region) was previously unidentified [17]. To understand whether this unique D/E substitution has impact on the antibody responses and parasite levels, we measured total IgG levels in a limited numbers of infected serum bearing the D/E substitution.…”
Section: Discussionmentioning
confidence: 86%
“…We recently undertook a sero-epidemiological investigation to understand the endemicity and host immune responses to P. vivax in Sanliurfa province [16]. In an earlier study, we observed increased sero-reactivity (∼54% IgG positivity) to the C-terminal region of the PvMSP1 19 antigen (one of the leading candidate vaccine antigens) in serum samples from infected individuals [16], and a further study showed limited and unique pvmsp1 polymorphisms in the parasite population in Turkey [17]. Therefore, comprehensive studies are needed to completely understand the immune responses to P. vivax antigens in this region.…”
Section: Introductionmentioning
confidence: 99%
“…However, the expected heterozygosity of Pvmsp1F3 was lower than that of Pfmsp2. Other studies have shown that Pvmsp1 has limited diversity compared with msp1 in other Plasmodium species 65 and the lower overall diversity compared with Pfmsp2 suggests its functional requirements may restrict diversity. Immune (balancing) selection 66 or recent reductions in population size due to control activities 64 may also influence the diversity measures differently.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to nucleotide polymorphisms, the central domain has large size variation and can be easily analyzed by using a polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) method (Cristiano et al, 2008). Large-scale genetic diversity analysis of P. vivax malaria and the genetic studies of re-emerging P. vivax malaria have been performed with several MSP polymorphic markers, including the Pv-MSP1 , PvMSP-3a and PvMSP-3β , using the PCR- RFLP genotyping method (Kirchgatter & del Portillo 1998; Cui et al, 2003; Leclerc et al, 2004; Kim et al, 2006; Yang et al, 2006; Veron et al, 2009; Prajapati et al, 2010; Zeyrek et al, 2010; Rungsihirunra et al, 2011). In this study, we evaluate the extent of diversity in field isolates of four P. vivax populations from China and Myanmar by PCR-RFLP of PvMSP-3a and PvMSP-3β genes.…”
Section: Introductionmentioning
confidence: 99%